Vascular plant taxa occurrences in exotic woodland and in natural and production forests on the Islands of São Miguel, Terceira and Pico (Azores) - Silva, Lurdes (2023)
The data presented here originated from field expeditions carried out between 2017 and 2018, within the framework of Forest-Eco2 project: "Towards an Ecological and Economic valorisation of the Azorean Forest". The project aimed to quantify the ecological value of the Azorean forests, including carbon accumulation and to design and propose measures that could further enhance forest sustainability. For that, 90 forest plots were sampled on three Azores islands - São Miguel, Terceira and Pico - equally distributed into natural forest, exotic woodland and production forest. The aim of this report is to further expand knowledge on biodiversity trends enclosed in the different forest types present in the Azores, by providing a list of the occurrences of the 105 different vascular plant taxa together with a brief characterisation of their origin and life-form.